2020
DOI: 10.1002/pd.5853
|View full text |Cite
|
Sign up to set email alerts
|

Prenatally detected isolated ventricular septum defects and the association with chromosomal aberrations—A nationwide register‐based study from Denmark

Abstract: Objective To evaluate the association between prenatally detected isolated ventricular septum defects (VSDs) and chromosomal aberrations in a nationwide study in Denmark. Method Nationwide, register‐based study with prospectively collected data including all singleton pregnancies from 2014‐2018. From the Danish Fetal Medicine Database, we retrieved data on maternal characteristics, first‐trimester biomarkers, pre‐ and postnatal diagnoses, genetic test results, and pregnancy outcomes. VSDs were considered isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…There is much disagreement in the literature regarding the association between isolated VSDs and chromosomal aberrations. Some reports suggest the association is low ( 16 , 17 , 20 ), while other studies point to an increased risk of chromosomal abnormalities ( 19 , 21 ). However, these studies either had small sample sizes or varied inclusion criteria, with no uniform definition of “isolated” VSDs, while some excluded cases with high-risk assessment in the first trimester, which may have changed the composition of second trimester fetuses presented for the survey.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is much disagreement in the literature regarding the association between isolated VSDs and chromosomal aberrations. Some reports suggest the association is low ( 16 , 17 , 20 ), while other studies point to an increased risk of chromosomal abnormalities ( 19 , 21 ). However, these studies either had small sample sizes or varied inclusion criteria, with no uniform definition of “isolated” VSDs, while some excluded cases with high-risk assessment in the first trimester, which may have changed the composition of second trimester fetuses presented for the survey.…”
Section: Discussionmentioning
confidence: 99%
“…Chromosomal microarray analysis (CMA), with high resolution and short turnaround time, is known to improve the detection of genomic aberrations and copy number variations (CNVs) compared to conventional karyotyping and has been found to have a pathogenic CNVs detection rate of approximately 6.0% in fetuses with ultrasound structural malformations ( 14 , 15 ). An increasing number of studies in recent years have employed CMA to identify CNVs in prenatal and postpartum subjects with isolated VSD ( 12 , 16 , 17 ). Although most published reports include large cohorts, investigators have studied isolated VSD as a subset of them, resulting in microscopic samples ( 18 20 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of fetal carriers of pathogenic CNV was not signi cantly different from the rate of the general pregnant woman population, which is approximately 1.6-1.7% [8]. Research conducted in pregnancies with low comprehensive risk assessment in early pregnancy and isolated VSD detected before delivery showed that the incidence of chromosomal abnormalities was 0.7%, which was lower than the incidence of chromosomal abnormalities in the general pregnant woman population [9]. It has also been reported that isolated muscular septal defect may be a benign variation [6].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we included only cases with major CHD, defined as a lesion usually requiring surgery within the first year of age. The results on isolated ventricular septal defects were not included in this study, as we have already published these data 21 . Moreover, pulmonary valve and aortic valve stenosis in cases with a biventricular heart were not included as individual diagnoses owing to the wide range of severity of these conditions.…”
Section: Methodsmentioning
confidence: 99%